Implications of The Conception of Ibn Rushid's Thought Towards Islamic Education - Komarudin, Omang; Zaenudin, Jejen; Supriyadi, Supriyadi; Kusnawan, Kusnawan (JASNA : Journal For Aswaja Studies, 2024)
Ibn Rushd, a renowned Islamic thinker, possesses extensive and profound scientific insights, particularly in the realm of Islamic education. As a Muslim intellectual, Ibn Rushd's expertise spans multiple disciplines, including philosophy, astronomy, jurisprudence, mathematics, and medicine. His passion for knowledge was nurtured by a family dedicated to science, leading him to study under distinguished scholars. His thoughts were profoundly influenced by Aristotle's rationality. This study aims to elucidate Ibn Rushd's contributions to Islamic education. The research employed a qualitative method with a literature study approach to analyze relevant literature., presented descriptively through data reduction, and concluded with key findings. The study reveals that Ibn Rushd advocated for integrating religious and general sciences and made significant efforts to harmonize philosophy with sharia (religion). His contributions to Islamic education include classifying students' comprehension levels according to their developmental stages and introducing various learning approaches and models, including the khitobi, jadal, and burhani methods. Additionally, he advocated for learning approaches grounded in reasoning, such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL)., and demonstrations.